Letter (copy) : Senor Pascual Tomas - Citrine, Walter, 1887-1983
026-0006-001 International. WMC/WJB/AT/1219. 28th August, 1939. The Rt. Hon. Viscount Halifax, K.G., G.C.S.I, G.C.I.E, Secretary of State for Foreign Affairs, Foreign Office, Downing Street, S.W.1. Dear Lord Halifax, SENOR PASCUAL TOMAS I am deeply indebted to you for the advice concerning the case of Senor Pascual Tomas, which you have been good enough to give me in your letter of the 25th instant. The procedure indicated shall be followed with the necessary discretion, and I will take the liberty of writing to you further when Senor Tomas replies. Again thanking you most sincerely for your kind consideration, I am, Yours faithfully, General Secretary. 292/946/26/6